Fantasy breakdown : a case study on organizational crisis communication and stakeholder reaction during mass product failure - Ruihley, Brody J.; Simmons, Jason; Billings, Andrew C.; Calabrese, Rich (London : Human Kinetics, Inc., 2018)
On the first Sunday of the National Football League's 2016–17 season, a technical issue caused ESPN's fantasy-football website and mobile application to fail. ESPN's product failure is no small problem and represented a major organizational crisis; with 7.1 million unique users, ESPN represents the largest provider of a multi-billion-dollar fantasy-sport industry. This case study examined ESPN's organizational communication strategy, as well as the stakeholder responses surrounding the failure of ESPN's fantasy-football website and application on the most anticipated day of the fantasy-sport season. Using content analysis and partnering with a social media data insights company, the study examined social media messages from both the organizational and consumer side of this fantasy-sport product failure. Through sampling 1,542 social media messages from a population of 11,881 unique comments via Twitter, the reactive nature of ESPN's messages and the direct responses from its consumers was ascertained.
Originally Published InRuihley, B., Simmons, J., Billings, A., & Calabrese, R. (2018). Fantasy breakdown: A case study on organizational crisis communication and stakeholder reaction during mass product failure. International Journal of Sport Communication, 11(4), 552–572.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; ESPN, Inc. -- Case studies; Communication in crisis management -- Case studies; Fantasy sports industry